Genetic and Environmental Risk Factors for Cannabis Use: Preliminary Results for the Role of Parental Care Perception. (21st March 2019) - Gerra, Maria Carla; Manfredini, Matteo; Cortese, Elena; Antonioni, Maria Caterina; Leonardi, Claudio; Magnelli, Fernanda; Somaini, Lorenzo; Jayanthi, Subramaniam; Cadet, Jean Lud; Donnini, Claudia
Abstract: Background: Vulnerability to cannabis use (CU) initiation and problematic use have been shown to be affected by both genetic and environmental factors, with still inconclusive and uncertain evidence. Objective: Aim of the present study was to investigate the possible interplay between gene polymorphisms and psychosocial conditions in CU susceptibility. Methods: Ninety-two cannabis users and ninety-three controls have been included in the study. Exclusion criteria were serious mental health disorders and severe somatic disorders, use of other drugs and alcohol abuse; control subjects were not screened to remove Reward Deficiency Syndrome (RDS) behaviors. A candidate gene association study was performed, including variants related to dopaminergic and endocannabinoids pathways. Adverse childhood experiences and quality of parental care have been retrospectively explored utilizing ACES (Adverse Children Experience Scale), CECA-q (Child Experience of Care and Abuse Questionnaire), PBI (Parental Bonding Instrument). Results: Our findings evidenced a significant association between rs1800497 Taq1A of ANKK1 gene and CU. Parental care was found to be protective factor, with emotional and physical neglect specifically influencing CU. Gender also played a role in CU, with males smoking more than females. However, when tested together genotypes and psychosocial variables, the significance of observed genetic differences disappeared. Conclusions: Our results confirm a significant role of Taq1A polymorphism in CU vulnerability. A primary role of environmental factors in mediating genetic risk has been highlighted: parental care could be considered the main target to design early prevention programs and strategies.